Systematic review of lung function assessment among youth and young adults e-cigarette users: Current tools and emerging methods - Nirul Isamuddin Nasir; Mohd Hasni Ja’afar; Norfazilah Ahmad (PLoS ONE, 2026)
Introduction This review focuses on the need to identify the lung function assessment tools used for young EC users. The objectives are to examine the current and emerging methods used in assessing lung function among young EC users, besides identifying the alterations in lung function following EC exposure measured by those tools. Methodology This systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 flow checklist. Six databases (Web of Science, PubMed, Scopus, Taylor & Francis, SAGE, and ScienceDirect) were searched in April 2025 for original articles published between 2016 and 2025. Quality appraisal of the eligible articles was conducted using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. Findings were synthesized using Narrative analysis. Results A total of 7 studies were included. Spirometry was used in all included studies; however, it is unable to detect subclinical lung alterations, as observed through ventilation-perfusion (V/Q) MRI and fractional exhaled nitric oxide (FeNO). Acute exposure to EC results in a decrease of FEV₁, FVC, PEF, and MEF₇₅ spirometric parameters, as well as reducing FeNO levels, while concurrently increasing exhaled breath temperature (EBT). Besides, an increase in V/Q mismatch and heterogeneity in ventilation is observed, with a reduction in perfusion heterogeneity. Chronic EC exposure causes a reduction in FEV 1 , PEF, FEV 1 /FVC, and FEF 25–75% , besides an increment of Carboxyhaemoglobin (HbCO) level. The assessment of the lung function post-EVALI in association with EC cessation revealed lung function improvement and increased diffusing capacity of the lung for carbon monoxide (DLCO). Conclusions Spirometry remains the first-line tool for assessing the lung function of young EC users; however, it often misses early lung dysfunction. Emerging methods (FeNO, DLCO, EBT, MRI, HbCO) increasingly complement this limitation. Tailoring multimodal assessment to exposure context, alongside screening and monitoring programs, may assist in early disease detection and prevent long-term respiratory effects.